Mucosal immunisation using the ovine nasopharyngeal route - Stanley, Amanda Christine (The University of Edinburgh, 2003)
The mucosal surfaces are a major site of pathogen entry and methods that stimulate the local immune response to provide a barrier to infection are highly desirable. The purpose of this study is to develop a novel intra-nasal vaccination strategy in sheep specifically targeting the mucosal-associated lymphoid tissue (MALT) in the nasopharyngeal tract. Initial studies demonstrated the location and composition of ovine nasal-associated lymphoid tissue, which was shown to be characteristic of an immune inductive site of MALT. Specialised epithelial cells with sparse irregular microvilli were revealed by electron microscopy within the follicle-associated epithelium (FAE). These cells were closely associated with lymphocytes in the underlying tissue and were characteristic of M cells, shown to be involved in the uptake of particulate antigenic material. Attempts to mark these M cells using lectins, alkaline phosphatase activity and antibodies against vimentin and cytokeratins proved unsuccessful. However, uptake of fluorescent microparticles into the epithelium could be demonstrated both in vitro and in vivo, suggesting that these M cells were functionally active. These initial studies suggested there was potential to stimulate an effective mucosal immune response by targeting ovine NALT with particulate antigen. A particulate delivery system using poly(D,L-lactide-coglycolide) (PLG), a biodegradable polymer, was then developed to deliver antigen to MALT through the M cells. Firstly, microparticles within the appropriate size range were produced, and protein encapsulation into these microparticles was optimised using BSA as a model protein. Protein encapsulation and release studies were performed on microparticles made from low and high molecular weight PLG polymers, and finally the stability and functionality of encapsulated proteins from Listeria monocytogenes were determined. These results allowed the optimal methods for particle preparation to be chosen.

An intra-nasal vaccination trial against Toxoplasma gondii was then performed in sheep. Proteins were extracted from toxoplasma tachyzoites and incorporated into PLG microparticles using the methods developed above. Sheep were vaccinated intranasally with soluble or particulate toxoplasma antigen, with blank particles as a negative control, or were infected with toxoplasma oocysts as a ii positive control. The potential for the use of cholera toxin as a mucosal adjuvant was also investigated. All sheep were challenged with an oral infection of toxoplasma oocysts at the end of the experiment. Sheep immunised with particulate toxoplasma antigen produced enhanced levels of both local and systemic antigen-specific IgA antibody. Some increase in systemic antigen-specific IgG antibody levels were measured in sheep immunised with particulate toxoplasma antigen and cholera toxin. After challenge with toxoplasma oocysts increased levels of both local and systemic IgG were measured more rapidly in all animals immunised with toxoplasma antigen, suggesting a secondary-type IgG response. Increased cellular immune responses and a corresponding increase in interferon gamma production were measured in sheep immunised with particulate toxoplasma antigens. A slight modification of the febrile response to toxoplasma infection could be observed in animals immunised with particulate toxoplasma antigen and cholera toxin, although none of the immunised animals were protected against the challenge infection. These studies have shown that the intra-nasal route stimulates both local and systemic immune responses, and shows promise as an effective route for mucosal immunisation.